REGIONAL DIALECT OF MANDAILINGNESE SHIFT IN BANDAR SELAMAT - Enni Maisaroh (Universitas Potensi Utama, 2018)
The purpose of this research was to investigate the factors influenced language shift of Mandailingnese in Bandar Selamat. Mandailingnese language is one of the vernaculars or Regional Languages in Indonesia that some of the society in Bandar Selamat. People are influenced by another language, because of several factors that people would not use their own language purely anymore. They would shift from their own language to another, which was known as language shift. Siregar (1998) found that language shift happen in the youth generation bilingual in Medan. According to Fasold (1984), language shift refers to changes in language use among a community of speakers such as when a community started to use on language in domain and functions in which its members had previously used another language and shift in the number of speakers of a language. In general, Mandailingnese Language shift in Bandar Selamat was influenced by bilingualism factors, economic factors, social factor, political factor, demographic factor, value and attitude factor, and the lack of Mandailingnese language competence factor. However, there are few different factors between the second and the third generation. Unlike the second generation, bilingual and economic factor are not significant factors for the third generation which influence them to shift from Mandailingnese language to Indonesian language since most of the subjects of the third generation are monolinguals.